The emergence of the conception of rationality in mainstream economics - Palacio-Vera, Alfonso (Iberian Journal of the History of Economic Thought, 2025)
Rationality is a loaded term. When we say that a person’s behaviour is rational, we hint that she acts as she ought to act. The normative dimension of rationality is often conflated, if not confounded, by social scientists. Historians of economic thought are not immune to this problem. The main thesis of this essay is that the earliest use of the term rationality in Economics appears in the work of Lionel Robbins and Paul Samuelson in the 1930s who identify rationality with consistency or transitivity of preferences. Using textual evidence, I show that the neoclassical economists who antedated them did not use the term ‘rationality’ and, although they did use the term ‘Logic,’ they did so without any normative pretensions. I identify three milestones in the process of emergence of an account of rationality in Economics. The first one was Jevons’ separation of Economics from Ethics and the demarcation of the scope of the Science of Economics. The second milestone was Carl Menger’s twin notions of economic goods and scarcity. The third and last milestone is Vilfredo Pareto’s reinterpretation of utility as a scale of preferences and its refinement by Hicks and Allen. Last, I briefly discuss some conceptual shortcomings of the prevailing account of rationality in Economics.